ANALISIS RESEPSI NASIONALISME DALAM VIDEO YOUTUBE ALFFY REV “WONDERLAND INDONESIA” - Zulatmiati "; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Wonderland Indonesia video is an offering to celebrate the 76th anniversary of the independence of the Indonesian state and is currently being discussed. Video Wonderland Indonesia contains a combination of 10 folk and national songs with contemporary musical arrangements that are displayed with stunning visuals. However, in line with the nationalism raised in this video, audiences who watch the Wonderland Indonesia video will bring up meanings according to their cultural and social background. This study aims to determine the dominant reading position, negotiated reading and oppositional reading of the audience towards nationalism in Wonderland Indonesia video. This research is a type of descriptive qualitative research that focuses on Stuart Hall reception analysis which focuses on encoding and decoding using purposive techniques to determine informants. The data obtained through the process of observation, in-depth interviews and documentation with six informants. The data analysis technique used is reception analysis which consists of data collection, interpretation and reception. While the technique of checking the validity of the data using tringulation. The results of the first study, four informants gave a dominant reception of nationalism in the Wonderland Indonesia video. The second is that two informants have the meaning of accepting but giving exceptions (negotiated). Third, none of the informants accepted the opposition's views. The difference in the way informants perceive nationalism in Wonderland Indonesia videos is caused by several factors, namely age, education, and experience. Keywords: Reception Analysis, Nationalism